Transformation of Electronics Learning in Higher Education through Augmented Reality to Improve Student Achievement - Anak Agung Gde Ekayana; Aniek Suryanti Kusuma; Ni Nyoman Parwati (Universitas Pendidikan Ganesha, 2025)
Electronics learning still faces challenges due to the dominance of lecture-based methods, leading to low learning outcomes. This study develops and evaluates a smartphone-based AR medium to improve achievement through interactive and immersive learning experiences. This research approach is based on the development model presented by Borg and Gall, but it has been tailored to the demands of the study to cover only five essential stages. The research design uses a one-group pretest-posttest model involving 30 students as participants. Data collection using questionnaires and tests. Analysis methods using validity, N-Gain test and T-test. The test results show that the media has a high level of validity, with a score of 0.88 from subject matter experts and 0.84 from media experts. Limited trial findings show that this learning medium is highly practical, with an achievement rate of 82.07%. This percentage grew to 85.67% throughout the full implementation stage, indicating that the usage of this medium becomes more efficient and follows the learning goals as it is deployed more broadly. The effectiveness test using t-test analysis showed a statistically significant improvement in learning outcomes (p = 0.000), with an N-Gain score of 0.58, which is in the moderate category. These findings indicate that AR learning media can improve student engagement, understanding, and performance in electronics learning. The study is limited to electronics courses, with unresolved issues in device compatibility and digital literacy. Future research should expand AR use to improve long-term retention.